Rural education as reported by school administrators from Sâo Paulo in the 1930s and 1940s - Celeste-Filho, Macioniro [UNESP] (My University, 2018)
In the 1930s and 1940s, the school system was consolidated into a new institutional organization in the State of Sâo Paulo, Brazil. School administrators and the regional teaching delegates organized a new level for primary education in this period. In urban areas, school groups were the model to be followed. However, how were the rural schools fairing? This chapter will present the vision of these teaching delegates and the calamitous situation of the rural education in Sâo Paulo during this period. This chapter will address the conflict between the everyday reality of the feasible school system and the targeted ideal for rural education in Sâo Paulo. The source material utilized for this study contemplates the reports of the school administrators preserved in the public archives of the State of Sâo Paulo.
Keywords: History of education; Isolated schools; Primary education of the state of Sâo Paulo; Rural schools